Manajemen Berbasis Sekolah dalam Meningkatkan Mutu Pendidikan di MA Unggulan KH. A. Wahab Hasbullah Jombang - Adawiyah, Robiatul; Sirojudin, Didin (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Education is the main foundation in the development of individuals and communities, until now the quality of education is still a topic of discussion in the community. The main role of education is to improve the quality of human resources, one of the solutions is through school based management (MBS) as resourve management to improve the quality of education. The purpose of the research is: (1) knowing the school based management in MA Unggulan KH. A. Wahab Hasbullah. (2) knows efforts to improve the quality of education in MA Unggulan KH. A. Wahab Hasbullah. (3) knowing the obstacles and solutions to improve the quality of education in MA Unggulan KH. A. Wahab Hasbullah. The method used in this study is qualitative descriptive with interviewing, observation, and documentation techniques. The date sources used in this study are primary sources and secondary sources. Based on the results of research, it can be concluded that MA Unggulan KH. A. Wahab Hasbullah has succeeded in implementing MBS effectively to improve the quality of education. In an effort to improve the quality of education, MA Unggulan KH. A. Wahab Hasbullah has implemented various schools based management strategies that focus on human resource development, teacher quality improvement, and more effective curriculum development. The strong leadership of the principal and the full commitment of all school staff are major factors in the successful implementation of MBS. The implementation of MBS is also supported by the use of technology to facilitate school administration management, learning, and communication between stakeholders. It has also helped to improve efficiency and effectiveness in the educational process in schools. In improving the quality of education, it mus also be accompanied by several obstacles and accompanied by concrete solutions.